Inicjatywy obywatelskie łodzian na rzecz neutralności klimatycznej miasta - Wasiak, Anna (Public participation in urban climate policy making: The example of Lodz, 2024)
The Anthropocene is not yet a known term for the geological era in which we live. Many scientific communities are calling for the adoption of this name, which would not only mean recognizing that predatory human activity has influenced the bad situation of our planet like never before. It would also mean official recognition of responsibility for the dramatic situation of loss of diversity. It should also be recognized that it is man as the perpetrator who should be responsible for stopping, but also partially reversing the trend. As modern individuals, we have no influence on shaping the policies of states and global corporations. However, we have a tangible impact on stopping the destruction and working for our local biodiversity. The article is an attempt to present what civic initiatives are undertaken by the inhabitants of Lodz.